Mechanical contribution of secondary phloem to postural control in trees: the bark side of the force. Issue 1 (4th August 2018) - Clair, Bruno; Ghislain, Barbara; Prunier, Jonathan; Lehnebach, Romain; Beauchêne, Jacques; Alméras, Tancrède
Summary: To grow straight, plants need a motor system that controls posture by generating forces to offset gravity. This motor function in trees was long thought to be only controlled by internal forces induced in wood. Here we provide evidence that bark is involved in the generation of mechanical stresses in several tree species. Saplings of nine tropical species were grown tilted and staked in a shadehouse and the change in curvature of the stem was measured after releasing from the pole and after removing the bark. This first experiment evidenced the contribution of bark in the up‐righting movement of tree stems. Combined mechanical measurements of released strains on adult trees and microstructural observations in both transverse and longitudinal/tangential plane enabled us to identify the mechanism responsible for the development of asymmetric mechanical stress in the bark of stems of these species. This mechanism does not result from cell wall maturation like in wood, or from the direct action of turgor pressure like in unlignified organs, but is the consequence of the interaction between wood radial pressure and a smartly organized trellis structure in the inner bark. Abstract : See also the Commentary on this article by Poppinga & Speck, 221 : 7–9 .